Metaphorical Symbols in Qur'anic Discourse: A Cognitive-Linguistic Analysis - Chaer, Hasanuddin; Rasyad, Abdul; Sukri, Sukri; Efendi, Mahmudi; Yaqin, Lalu Nurul (Universitas Muhammadiyah Surakarta, 2025)
This article examines the relationship between language, thought, and religious experience in Islamic theology using George Lakoff’s cognitive linguistic framework. Focusing on theological metaphors in selected Qur’anic verses, Al-Baqarah 255 (Ayat al-Kursi), An-Nur 35, Ibrahim 24–25, Al-Hadid 13, and Ar-Ra’d 28, it applies conceptual metaphor theory to reveal how the Qur’an conveys theological and spiritual meanings through cognitive structures. The study proceeds in four stages: identifying and categorizing Qur’anic theological metaphors; analyzing their structure and function through cognitive linguistics; exploring how metaphor links language with religious thought; and interpreting the results to assess their theological significance. The findings show that Qur’anic metaphors transform abstract theological concepts into concrete, accessible ideas, deepening Muslims’ spiritual understanding. This research contributes to cognitive linguistics and religious studies by demonstrating how metaphor serves as a bridge between divine revelation and human cognition. Future studies could develop cognitive linguistic approaches for teaching theology, emphasizing metaphor as a key tool for conceptual and spiritual comprehension.